Proposal to Minimize the European Dependence on Russian Natural Gas for Space Heating and Sanitary Hot Water by Using Heat Pumps - Juanico, Luis Eduardo (2022)
This work proposes a strategy to minimize the European dependence on natural gas by using modern heat pumps for space heating and sanitary hot water demands. The monthly efficiencies of three different kinds of heat pumps (air-to-air Split and air-to-water coupled to infloor or hot-water-radiator systems) are calculated for temperate (Barcelona), cold (Berlin), and very cold (Helsinki) climates. The split and infloor heat pumps provide higher efficiencies (around 410 % in Barcelona, 350 % in Berlin, and 320 % in Helsinki); on the other hand, radiator heat pumps get lower efficiencies (about 210 %). The annual electricity expenses for average 100 m 2 4-person departments are calculated, ranging from €500-800 in Barcelona to €1000-1900 in Helsinki, and €1200-2200 in Berlin, which are similar to current expenses in natural gas. Furthermore, a strategy of time-distributed consumption is studied, which reduces the dweller expense and stress on electricity grids. It gets savings up to 28 % and does not increase the electrical consumption during peak-tariff periods. Thus, we recommend using heat pumps working on hourly-tariffs schemes (instead of a single 24x7 tariff) for the current transition and future scenarios based on renewable energies.